Stepping out across the Karoo retro-foreland basin: Improved constraints on the Ecca-Beaufort shoreline along the northern margin. (January 2022) - Groenewald, David P.; Day, Michael O.; Penn-Clarke, Cameron R.; Rubidge, Bruce S.
Abstract: The Karoo Supergroup of South Africa, internationally renowned for its almost continuous Carboniferous to Jurassic record of deposition in a foreland basin setting, hosts an unparalleled record of fossil tetrapods that provides unique insight into terrestrial biodiversity change over this extended period. Understanding of the litho-, bio- and chronostratigraphy of the Karoo Basin has greatly improved in recent years but most work has focused on the thicker and better-exposed rocks in the basinal foredeep. A core issue that has remained ambiguous is the stratigraphic placement of the diachronous Ecca-Beaufort contact, for which different criteria have been used during mapping in different parts of the main Karoo Basin. Comparison of biostratigraphy and contrasting lithological facies changes with those in the better-studied foredeep enabled us to revise the lithostratigraphy of the Ecca and Beaufort groups in the distal part of the main Karoo Basin. The presence of proximal marine facies associations in the distal sector conform with the definition of the Waterford Formation of the Ecca Group, so far recognised only in the southern foredeep. The upper contact of the Waterford Formation represents a change from a subaqueous to a subaerial delta plain depositional environment and marks the boundary between the Ecca and Beaufort groups, as in the south. This has consequences for Beaufort Group stratigraphic subdivision in the distal sector of the Karoo foreland basin. Highlights: Ecca-Beaufort contact represents the Karoo palaeoshoreline throughout the basin. The Waterford Formation (Ecca Group) is present in the north of the Karoo Basin. Biostratigraphy reveals 6 Ma hiatus in Permian rocks in the southern Free State. Normandien Formation is synonymised with the Balfour Formation. Out of phase deposition and missing biozones support the reciprocal foreland model.